Kasnodon Ukraine: History/Culture/Presumptions and Helping Developing Nations Move Forward - R. Scott Colson, Esq. (SocioEconomic Challenges)
This article chronicles some of my work in Ukraine in the late 90’s until 2006 especially in the Donbas Region of Ukraine. This was a program funded by USAID through the US-Ukraine Foundation to promote democratic development in cities in Ukraine by establishing partnerships between American cities and Ukrainian cities. The partnership between Birmingham and Krasnodon became a model for the entire program and regular communication continued until the war in Donbas ended communications for most people. The program included topics including citizen involvement, water/sewer, transparency, economic development, education, transportation and public health. I served under five different Mayoral administrations for 35 years in Birmingham and worked on a wide range of issues in that time including public safety, youth programs, arts and museums, international programs and economic development. This experience allowed me to access resources in Birmingham on a broad range of issues and create relationships between professionals in both communities. It also was the source of my love and admiration for the Ukrainian people which continues to this day in my role as Honorary Consul for Ukraine to Alabama. Much has changed in Ukraine during the 25 years I have worked with them. This article chronicles a couple of stories that exemplify some of the hazards and opportunities I have been a part of and hopefully can add to the wisdom and understanding of our two nations. The younger generation of Ukrainians born to independence are showing more openness to change and attempting good new things. Helping them channel their idealism and energy in the face of threats and inertia is an honor and a real opportunity to fight for freedom.